The feasibility of laparoscopically assisted, hysteroscopic removal of interstitial pregnancies: A case series. Issue 10 (5th July 2021) - Niu, Xiaocen; Tang, Yibo; Li, Songyue; Ni, Shanshan; Zheng, Wanren; Huang, Lili
Abstract: Objective: The study objective was to assess the feasibility of the management of interstitial pregnancy by laparoscopically assisted hysteroscopic removal. Methods: This retrospective study included a case series of 17 patients who were diagnosed interstitial pregnancy with dilated proximal tubal ostium by transvaginal ultrasonography at the Women's hospital, School of Medicine, Zhejiang University between August 2017 and October 2020. Laparoscopically assisted hysteroscopic removals of the products of conception were performed. Various data were collected including age, surgical and obstetric history, gestational age, preoperative symptoms, human chorionic gonadotropin level and ultrasonography results. The outcomes measured were intraoperative bleeding, pathologic findings, conversions. Results: Eleven cases were successfully resected the interstitial gestational products with laparoscopically assisted hysteroscopy. There were four cases failed of hysteroscopic removal, for the proximal tubal ostia were too small for the surgical instruments to enter. Then cornual wedge resections were performed. Two cases were identified as intramural pregnancy by hysteroscopic and laparoscopic view. Most of the intramural pregnancy tissue of one patient was removed by hysteroscopy. The other one converted to laparoscopy. Conclusion: Laparoscopically assisted hysteroscopic management could be a feasible surgical option to interstitial pregnancies. Further clinical studies are needed to establish detailed criteria to select the appropriate cases for hysteroscopic management.